Sociodemographic and clinical profiles of individuals with opioid dependence syndrome presenting to a tertiary care center in Assam: A retrospective review - Pranjal J. Chakravarty; Tathagata Mahintamani; Diptadhi Mukherjee; Partha P. Daimary; Hemanta Dutta (Indian Journal of Psychiatry)
Background: Opioid dependence is a critical public health issue in Northeast India, with limited data available on the affected population. Aim: This study examines the sociodemographic and clinical profiles of opioid-dependent individuals in Assam. Methods: A retrospective review was conducted of 238 patients diagnosed with opioid dependence at a tertiary care addiction treatment center in Assam, covering records from January 2022 to January 2023. Results: The sample consisted mainly of young, married males (median age 25 years), with a median 24-month dependence duration. Heroin was the primary opioid, and 55.5% had a history of injecting drug use (IDU). Among injection drug users (IDUs), 83.3% were positive for HCV, 9.8% for HBV, and 28.0% for HIV. Early onset of heroin use and unmarried status were linked to higher HCV prevalence, while HIV prevalence showed no significant sociodemographic associations in IDUs. Conclusion: The high prevalence of IDU and associated infections underscores the need for targeted interventions and comprehensive treatment resources for opioid users in Assam.